Preparation and evaluation of a controlled drug release of repaglinide through matrix pellets: in vitro and in vivo studies. (September 2014) - Tavakoli, Naser; Minaiyan, Mohsen; Tabbakhian, Majid; Pendar, Yaqub
Abstract Repaglinide, an oral antidiabetic agent, has a rapid onset of action and short half-life of approximately 1 h. Designing a controlled release dosage form of the drug is required to maintain its therapeutic blood level and to eliminate its adverse effects, particularly the hypoglycaemia. Repaglinide sustained release matrix pellets consisting of Avicel, lactose and different polymers were prepared using extrusion–spheronisation method. The effect of different formulation components on in vitro drug release were evaluated using USP apparatus (paddle) for 12 h in phosphate buffer. The optimised formulation was orally administrated to normal and STZ induced diabetic rats. Most pellet formulations had acceptable physical properties with regard to size distribution, flowability and friability. Repaglinide pellets comprising Avicel 50%, lactose 47% and SLS 1% were released 94% of its drug content after 12 h. The optimised formulation was able to decrease blood glucose level in normal rats and those with diabetes throughout 8–12 h.